2006
DOI: 10.1080/09546630600688515
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in dermatology: A review of the last 20 years

Abstract: Adherence to topical therapy among dermatology patients is difficult to measure reliably, hence the few articles available on this topic. A small number of studies using new electronic monitoring technology have shown that dermatology patients have low adherence rates to treatment regimens. There are socioeconomic, cognitive, and psychological factors that contribute to non-adherence among patients. Improving patient knowledge and the doctor-patient relationship are ways to improve patient adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 27 publications
1
77
0
3
Order By: Relevance
“…The time, date and time elapsed since the bottle was last opened is recorded every time the cap is unscrewed. Provided the pharmaceutical formulation is suitable, the bottles can be used not only for solid and liquid, but also for semisolid presentation forms [34]. This monitoring system tends to furnish lower adherence values than the patient interview [35,36] or the determination of medication usage [32] and, consequently, is often regarded as today’s reference standard despite the costs and limited usage.…”
Section: Resultsmentioning
confidence: 99%
“…The time, date and time elapsed since the bottle was last opened is recorded every time the cap is unscrewed. Provided the pharmaceutical formulation is suitable, the bottles can be used not only for solid and liquid, but also for semisolid presentation forms [34]. This monitoring system tends to furnish lower adherence values than the patient interview [35,36] or the determination of medication usage [32] and, consequently, is often regarded as today’s reference standard despite the costs and limited usage.…”
Section: Resultsmentioning
confidence: 99%
“…4). The duration of treatment may also be of importance, since it has been shown that first-time users tend to be more adherent than patients who transitioned from previous therapies [27]. We did not see any differences in MPR between the patients who got their first biologic and the patients who were switched from another biologic.…”
Section: Discussionmentioning
confidence: 45%
“…Poor quality of life, depression, and resignation on part of the patient have a negative effect on compliance [27]. A positive attitude to medication can result in a measurable improvement of adherence [20].…”
Section: Discussionmentioning
confidence: 99%
“…Uma revisão de literatura sobre o tema mostrou que pouco se tem estudado sobre adesão em pacientes com dermatoses e um pequeno número de estudos encontrados que tratavam da utilização de tecnologia de monitoramento eletrônico mostrou que os pacientes dermatológicos apresentam baixas taxas de adesão aos regimes de tratamento, o que reforça a necessidade de intervenções para melhorar adesão. Existem fatores sócio-econômicos, emocionais e comportamentais que contribuem para a não-adesão, o que pode ser modificado com aumento do conhecimento do paciente sobre sua doença e sobre o tratamento, com uma boa relação médico-paciente (Hodari, Nanton, Carrol, Feldman & Balkrishnan, 2006) e também com intervenção psicológica .…”
Section: Intervenção Psicológicaunclassified